MONEY ATTITUDE DAN PERILAKU BERHUTANG PADA PENGGUNA E-COMMERCE - Perdana, Endika; Akidah, Syahla Nur; Rohani, Alia; Sartika, Siska; Darmayantie, Astie (Jurnal Ilmiah Ekonomi Bisnis, 2024)
The enhancement of service quality by adding new features is considered one of the critical determinants of the growing use of e-commerce platforms today. The availability of various payment options, including installment facilities, not only facilitates transactions but also increases the potential for debt-related behavior. This phenomenon is intriguing and essential to investigate, as poorly managed debt behavior can negatively affect an individual's financial condition and stability. This study aims to analyze the influence of money attitudes on debt behavior among e-commerce users. The research involved 169 respondents aged 17 and older who had used installment payment methods more than twice in the past month. Data were collected using the money attitude and debt behavior scales and analyzed using IBM SPSS Statistics version 25. The results indicate that money attitude significantly influences debt behavior, contributing 28%. Additionally, debt behavior was more prevalent among women and Generation Z. This research provides valuable insights for designing financial education strategies and more prudent payment policies within e-commerce, particularly for groups more vulnerable to excessive debt.